Gender, language and labour: gender perception of Estonian and Russian occupational titles - Kaukonen, Elisabeth; Oskolskaia, Polina; Lindström, Liina; Marling, Raili (Frontiers in Communication, 2025)
IntroductionCurrent research on occupational gender stereotypes in language has indicated that gender bias is influenced by various aspects, including social knowledge about roles associated with either men or women as well as linguistic information. This study focuses on gender perception of language users of Estonian and Russian. The former is a grammatically genderless Finno-Ugric language, while the latter has grammatical gender. Based on previous studies, we investigate whether occupational gender stereotypes in these languages are evoked by social beliefs, stereotypes and other extralinguistic factors and/or by language. Additionally, we examine whether the extent of gender bias varies across these languages.MethodsTwo separate web-based Likert scale surveys were conducted, one in Estonian and the other in Russian. The surveys included sentences featuring 36 occupational titles in Estonian and 34 in Russian. Data were analyzed using R software, employing principal component analysis and binomial logistic regression models.ResultsA total of 581 Estonian-speaking as well as 326 Russian-speaking participants took part in the study. Analyses revealed that biased responses were primarily influenced by social knowledge, followed by the influence of language. In Russian, results indicated that stereotypical information often overrides linguistic cues.DiscussionThe results suggest that gender perceptions are shaped by social knowledge and stereotypes, which work in cooperation with language. Based on these results, we propose that Estonian, while grammatically genderless and thus seemingly gender neutral, evokes as much or even more bias than grammatically gendered Russian.